2008
DOI: 10.2214/ajr.07.3865
|View full text |Cite
|
Sign up to set email alerts
|

Role of Diffusion-Weighted MRI in the Detection of Early Active Sacroiliitis

Abstract: DWI is a sensitive, fast sequence and does not require a contrast agent, which makes it a good and cost-effective alternative for imaging sacroiliac joints. DWI also offers the possibility of quantifying diffusion coefficients of the lesions, which helps to discriminate between normal and involved subchondral bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
85
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 27 publications
(24 reference statements)
6
85
0
2
Order By: Relevance
“…In some studies, contrastenhanced T 1 -weighted sequences were found to be more sensitive than STIR and fat-suppressed T 2 -weighted images. 4 Up to date, many studies have been performed on detection of sacroiliitis with DWI. Bozgeyik et al 4 studied 42 patients with chronic low back pain (suspected spondyloarthropathy).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In some studies, contrastenhanced T 1 -weighted sequences were found to be more sensitive than STIR and fat-suppressed T 2 -weighted images. 4 Up to date, many studies have been performed on detection of sacroiliitis with DWI. Bozgeyik et al 4 studied 42 patients with chronic low back pain (suspected spondyloarthropathy).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Musculoskeletal abnormalities assessed by DWI are muscle, cartilage and soft tissue diseases, several spinal abnormalities, and bone marrow edema. 4 Acute osteoporotic and metastatic fractures of vertebra, spinal infection and malignancy can be discriminated by the help of DWI. Detection of skull metastasis and traumatic bone marrow edema are also possible with DWI.…”
mentioning
confidence: 99%
See 3 more Smart Citations